2006
DOI: 10.1002/prot.20982
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of Salmonella typhimurium YeaZ, an M22 O‐sialoglycoprotein endopeptidase homolog

Abstract: The Salmonella typhimurium "yeaZ" gene (StyeaZ) encodes an essential protein of unknown function (StYeaZ), which has previously been annotated as a putative homolog of the Pasteurella haemolytica M22 O-sialoglycoprotein endopeptidase Gcp. YeaZ has also recently been reported as the first example of an RPF from a gram-negative bacterial species. To further characterize the properties of StYeaZ and the widely occurring MK-M22 family, we describe the purification, biochemical analysis, crystallization, and struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
59
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 51 publications
7
59
0
Order By: Relevance
“…25 An ATP-ase activity for HiYjeE was observed, although another report revealed tight binding of ADP but only slow hydrolysis of ATP once contaminating ATPases were removed. 26 Crystal structures for YeaZ from Escherichia coli (Ec), 27 Salmonella typhimurium (St), 28 Thermotoga maritime (Tm), 29 and Vibrio parahaemolyticus(Vp) 30 have been determined. YeaZ has a 2-lobed structure which belongs to the ASKHA superfamily.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…25 An ATP-ase activity for HiYjeE was observed, although another report revealed tight binding of ADP but only slow hydrolysis of ATP once contaminating ATPases were removed. 26 Crystal structures for YeaZ from Escherichia coli (Ec), 27 Salmonella typhimurium (St), 28 Thermotoga maritime (Tm), 29 and Vibrio parahaemolyticus(Vp) 30 have been determined. YeaZ has a 2-lobed structure which belongs to the ASKHA superfamily.…”
mentioning
confidence: 99%
“…In order for YeaZ to bind nucleotides it seemed that relative domain movements and/or binding to a partner protein might be necessary. 28 It has been proposed that an alternative dimer interface AB/form 2, observed in the TmYeaZ crystal structure, if utilised in the YgjD-YeaZ complex, might allow nucleotide binding to extend from YeaZ across the heterodimer boundary. 29,30 It was further suggested that the different conformational states of these two dimeric complexes could form the basis for a switching mechanism between partner proteins.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The YeaZ proteins form a family assigned as COG1214 (http://www.ncbi.nlm.nih.gov/Structure /cdd/cddsrv.cgi?uidϭCOG1214) which is annotated as "Inactive homolog of metal-dependent proteases, putative molecular chaperone." A recent crystal structure of S. enterica serovar Typhimurium YeaZ shows that the protein is part of the HSP70 actin-like-fold (HALF) protein family and suggests the likelihood that upon domain rearrangement, the protein would bind a nucleotide (51). Purification of an affinity-tagged version of YeaZ produced at native levels identified YgjD as a copurifying partner (9), suggesting that these two homologous proteins form a complex in vivo.…”
mentioning
confidence: 99%